Alignment of business in robotic process automation - Ning Zhang (International Journal of Crowd Science, 2019)
Purpose - This paper aims to find out how business aligns with robotic process automation (RPA) and whether the alignment has the same factors as for IT–business alignment. Design/Methodology/Approach - Condition configurations for positive and negative impact for business alignment with RPA. Findings - The positive and negative configurations that possibly impact business alignment with RPA. Research limitations/implications -There are some human instincts during conditions dichotomization and limited number of cases. Practical implications- The findings can be used to guide practice application in real industry. Originality/value- This paper adopted crisp-set qualitative comparative analysis to find condition configurations for alignment of business and RPA for more generalization.